1998
DOI: 10.1046/j.1469-1809.1998.6240307.x
|View full text |Cite
|
Sign up to set email alerts
|

Major gene control of human body height, weight and BMI in five ethnically different populations

Abstract: Pedigree samples were collected from five ethnically and geographically different populations : Kirghizians, Turkmenians, Chuvashians, Israelis and Mexicans. All studied individuals were assessed for body height, weight and BMI. The sample size in the studied pedigrees ranged from 381 to 1811 individuals. Segregation analysis of these traits preliminarily adjusted for sex and age was performed by means of program package  that provides parameter estimates for the major gene effects, for the residual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 22 publications
1
58
0
1
Order By: Relevance
“…This would be in contrast to the results of a segregation analysis in which height was predicted by a putative major gene, explaining 37 -53% of the variance. 36 A more recent analysis 20 also found that a model that included a major recessive gene and residual polygenic effect (mixed-recessive model) best fitted the height data. However, the difference between the mixed-recessive model and the polygenic model was very small and both models fitted the data equally well when spouse correlations were included in the model.…”
Section: Discussionmentioning
confidence: 99%
“…This would be in contrast to the results of a segregation analysis in which height was predicted by a putative major gene, explaining 37 -53% of the variance. 36 A more recent analysis 20 also found that a model that included a major recessive gene and residual polygenic effect (mixed-recessive model) best fitted the height data. However, the difference between the mixed-recessive model and the polygenic model was very small and both models fitted the data equally well when spouse correlations were included in the model.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, height has been considered a paradigm of complex genetics as its familial aggregation is likely the result of multiple genetic and environmental factors, although the dissection of the genetic factors may prove to be more tractable than other phenotypes (Hirschhorn et al 2001). Segregation analyses have suggested that the observed variation may be due to at least one major recessive gene (Xu et al 2002) that could account for 37-53% of the variance for both height and weight (Ginsburg et al 1998), with a significant polygenic background (Xu et al 2002). Recent studies have reported the heritability for height in the range 0.69-0.98 (Hirschhorn et al 2001;Perola et al 2001;Deng et al 2002;Wiltshire et al 2002;Xu et al 2002;Mukhopadhyay et al 2003;Wu et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Carter and Marshall, 1978;Ginsburg et al, 1998). It is well established that people tend to marry people of similar characteristics, be it education, socio-economic status, or height.…”
mentioning
confidence: 99%